The Influence of Individual Characteristics, Competencies and Organizational Culture towards the Quality of Work Life and Employee Performance Outsourcing Company in East Java Province - Gamal, Ahmad; Soelistya, Djoko (Archives of Business Research, 2019)
The era of globalization and the digital age encourages companies to improve the quality of human resources with the expectation of being able to compete and survive. The increasingly rigorous competition sparked the company to first settled themselves. Start of the development of human resources, the software always up date and the company's operational system is always the latest and innovative products. The purpose of this research is to examine and analyze the influence of individual characteristics, competencies and organizational culture towards the quality of work life and employee performance outsourcing company in East Java Province The technique used is the analysis of path analysis with SEM (Structural Equation Modeling) with the program SPSS version 23 and AMOS 18. The population in this research is outsourcing company in East Java Province and the sample numbered 165 employees. The results of the discussions can be concluded that the competence effect significantly to quality of work life, Individual characteristics effect significantly to quality of work life, Organization culture effect significantly to quality of work life, the Competence effect significantly to performance of employees, Individual characteristics effect significantly to performance of employees, Individual characteristics effect significantly to performance of employees, Organization culture effect significantly to performance of employees, and Quality of work life effect significantly to performance of employees